INFLUENCE OF PHYSICAL CULTURE INNOVATIVE MEANS ON FUNCTIONAL STATE OF SECOND MATURITY WOMEN - Konakova, O.Y. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Purpose: to find influence of physical culture innovative means (combination of Pilates - exercises for body and mind - and program Port de bras (movements of arms and body)) on functional state of second maturity women. Material: 22 women of age from 50 to 55 were tested; they were divided into main and control groups. Control group practiced health related swimming; experimental group was trained by system Pilates and program Port de bras with application of special equipment. Results: it was found, that for confident changes in women’s functional systems it was necessary to practice trainings in zone of sub-maximal load (75-85% from maximal oxygen consumption); trainings in zone of low intensity do not give confident health related effect. Conclusions: At low and below average women’s physical fitness it is necessary to practice health related trainings in zone of low intensity (mean heart beats rate -90-115 beats per minute). For increasing trainings intensity it is necessary to raise women’s physical fitness.